Catholic LGBTQ people - Brandão, Ana Maria (2016)
This entry examines the official position of the Roman Catholic Church regarding homosexuality and transgenderism, as well as its potential effects on the relationship between the gender and/or sexual identities of Catholic LGBTQ people and their confessional or religious identities. Next, it shows how the relationship of Catholic LGBTQ people with their faith may lead to a conflict between those identities. The main psychological effects of this conflict, as well as the ways identity contradictions are managed and/or resolved, are also examined. Finally, the influence of the wider sociocultural context and of the specific characteristics of the Catholic confession on that process is highlighted.